2016
DOI: 10.1209/0295-5075/115/47001
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality-driven phonon softening and incipient charge density wave instability in TiS 2

Abstract: Density functional theory and density functional perturbation theory are used to investigate the electronic and vibrational properties of TiS2. Within the local density approximation the material is a semimetal both in the bulk and in the monolayer form. Most interestingly we observe a Kohn anomaly in the bulk phonon dispersion, which turns into a charge density wave instability when TiS2 is thinned to less than four monolayers. Such instability, however, disappears when one calculates the electronic structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 62 publications
2
51
0
Order By: Relevance
“…in TiS 2 . 31,32 In the case of TiS 2 we found that for a 12 atoms unit cell (2X2 unit cell), the distorted and the perfectly symmetric structure differ by only ∼ 0.04 eV (∼ 0.004 eV per atom). It turns out that due to similar energy differences, the CDW phases of other compounds e.g.…”
mentioning
confidence: 84%
“…in TiS 2 . 31,32 In the case of TiS 2 we found that for a 12 atoms unit cell (2X2 unit cell), the distorted and the perfectly symmetric structure differ by only ∼ 0.04 eV (∼ 0.004 eV per atom). It turns out that due to similar energy differences, the CDW phases of other compounds e.g.…”
mentioning
confidence: 84%
“…charge doping suppresses the instability [48,49]), it is unclear to what extent this prediction is robust or resulting partially from a cancellation of errors. We note that for TiS 2 , PBE calculations predict a metallic electronic structure for both bulk and monolayer forms and phonon softening, with imaginary frequencies in the monolayer case [51]. Experimentally, the bulk material exhibits a gap of ∼ 0.7 eV [52] and no sign of CDW or phonon softening were reported.…”
mentioning
confidence: 71%
“…In some of these compounds, our phonon band structures show Kohn anomalies due to their small or zero band gaps [136][137][138][139]. When compared to their bulk counterparts [60], the Kohn anomalies appear at M for both bulk and monolayer TiS 2 and TiSe 2 .…”
Section: Resultsmentioning
confidence: 99%